Traditional and Conventional Social Communication Processes for Increasing Tolerance and Harmonization of Inter-Religious Communities in Indonesia - Muhammad Aras; Alexander A. S. Gunawan (Bina Nusantara University, 2019)
This research focused on the social communication process for increasing tolerance and harmonization of inter-religious communities in Indonesia. This research method used the case study design. Research data of this case study were collected through observations and in-depth interviews. The results indicate that the process of social communication between religions takes place dynamically in the community. It involves mutual interactions and respect for each other according to social norms and values adopted by the local community. By interacting and respecting each other, the social life of the community can be maintained to be harmonious, safe, comfortable, full of tolerance and harmony, and coexist in religious, cultural, ethnic, racial, and ethnic diversity. Based on research findings, all can be done through the social communication process for increasing tolerance and harmonization of social life among religious communities in Indonesia that the process of social communication is directly referred to as traditional and conventional communication.